The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1159/000479915
|View full text |Cite
|
Sign up to set email alerts
|

Association Between C1q/TNF-Related Protein-1 Levels in Human Plasma and Epicardial Adipose Tissues and Congestive Heart Failure

Abstract: Background/Aims: C1q and tumour necrosis factor-related protein 1 (CTRP1) possesses anti-atherogenic and anti-inflammatory effects. This study investigated whether the CTRP1 levels in the plasma and epicardial adipose tissue (EAT) were associated with congestive heart failure (CHF) and to disclose possible molecular mechanisms. Methods: Plasma and tissue samples were obtained from subjects with or without CHF. Plasma levels of CTRP1 were measured by ELISA. The mRNA levels of CTRP1 and inflammatory cytokines we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
22
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 27 publications
3
22
0
Order By: Relevance
“…For instance, CTRP1 forms an oligo‐heterotrimer with CTRP6, and is known to enhance glucose uptake and insulin sensitivity . Elevated levels of CTRP1 have been associated with BMI, T2DM, nonalcoholic fatty liver disease (NAFLD), congestive heart failure (CHF), and chronic kidney disease progression . CTRP3, also known as cartonectin, regulates glucose homeostasis and exhibits anti‐inflammatory immunomodulatory role .…”
Section: Discussionmentioning
confidence: 99%
“…For instance, CTRP1 forms an oligo‐heterotrimer with CTRP6, and is known to enhance glucose uptake and insulin sensitivity . Elevated levels of CTRP1 have been associated with BMI, T2DM, nonalcoholic fatty liver disease (NAFLD), congestive heart failure (CHF), and chronic kidney disease progression . CTRP3, also known as cartonectin, regulates glucose homeostasis and exhibits anti‐inflammatory immunomodulatory role .…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, there have been many studies investigating serum levels of CTRP1 and coronary artery disease. Studies have shown that CTRP1 is a marker of human atherosclerosis and promotes atherosclerosis in [17][18][19] . The serum of the three-vessel disease had a high concentration of CTRP1 than the single-vessel disease, which was consistent with our findings.…”
Section: Discussionmentioning
confidence: 99%
“…It is primarily expressed and secreted by the stromal-vascular cells and visceral adipose tissue and marginally by the zona glomerulosa of the adrenal cortex and vascular wall tissue [9]. Plasma CTRP1 levels exhibited in humans significant association with body mass index (BMI) [10], type 2 DM [11] and congestive heart failure [12] and is thought to play a role in several metabolic pathways. As CTRP1 enhances glucose uptake and insulin sensitivity [13], it has been proposed as a negative feedback regulator in DM.…”
Section: Introductionmentioning
confidence: 99%